Assessing Food Security Levels Using the Food Security and Vulnerability Atlas Approach in Ogan Komering Ulu Regency, South Sumatra - Munajat; Fifian Permata Sari; Ema Pusvita (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Food is a priority human need for survival. The evaluate population's level of food security in Ogan Komering Ulu (OKU) Regency, South Sumatra. This study includes mapping and measuring food vulnerability based on the main indicators: availability, accessibility, and food utilization. The purposive sampling method was used to select the research location, which covers 157 villages and 13 sub-districts in OKU Regency. Primary data were obtained through field observations and surveys, while secondary data were obtained from various official sources. The results showed that the Food Security Index (IKP) of OKU Regency was in the moderate category, with variations in the level of food security in each sub-district. The vast agricultural land increases food availability, but low nutritional awareness and stunting rates in children challenge good food accessibility and utilization. In addition, the analysis found groups of people vulnerable to food insecurity, especially in remote areas. These findings will help policymakers create better strategies to address food security issues in the OKU Regency. Contribution to Sustainable Development Goals (SDGs): SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 11: Sustainable Cities and Communities